Brown locusts, Locustana pardalina, host fluconazole-resistant Candidozyma (Candida) auris, closely related to Clade III clinical strains - Ogundeji, Adepemi; Bello-Akinosho, Maryam; Swart, Vaughn; Featherston, Jonathan; Cason, Errol D; Bolsenbroek, Armand; Beneke, Carel; Musoke, Jolly; Baker, Tyla; Ismail, Arshad; Sebolai, Olihile; Albertyn, Jacobus; et al. (Medical mycology (Oxford), 2025)
Abstract The environmental niche and mode of transmission from the environment to humans of the emerging pathogenic yeast, Candidozyma (Candida) auris is a subject of speculation, with hypotheses including avian species and marine environments. Interestingly, yeasts related to Candidozyma auris have been repeatedly observed associated with various insects. This prompted us to investigate a thermophilic insect, Locustana pardalina, as a possible host for C. auris. Here, we report the isolation and identification of three C. auris strains from the gut of L. pardalina as well as the phenotypic characterisation of one of these isolates. Interestingly, the isolate was able to survive at 50°C and grew at 15% NaCl. In addition, it was susceptible to the tested disinfectants and antifungals, except fluconazole. Genome sequencing and single-nucleotide polymorphism analyses placed the isolate in Clade III, which is common in South African hospitals. This highlights the potential role of thermotolerant insects in the evolution and dissemination of emerging pathogenic yeasts. Lay Summary The study investigates the presence of the pathogenic yeast, Candidozyma auris, in brown locusts. The characterised strain was related to hospital strains previously found in South Africa and was resistant to fluconazole. This highlights the potential role of insects in spreading this pathogen.